Sistem Monitoring Kadar Gas Metana (Ch4), Gas Amonia (Nh3) Dan Gas Karbon Dioksida (Co2) Pada Tempat Pembuangan Sampah Untuk Pencegahan Penyakit Ispa Berbasis Wireless Sensor Network - Lova Nugroho; Rachmad Saptono; Aad Hariyadi (Politeknik Negeri Malang, 2021)
The existence of Wireless Sensor Network (WSN) technology is used to create a system for monitoring gas levels at landfills, in particular, the three gases to be monitored, namely methane gas (CH4), ammonia gas (NH3) and carbon dioxide gas (CO2) which can cause disease. Respiratory tract infection. This monitoring system utilizes Wireless Sensor Network technology so that it can monitor a more comprehensive area using a large number of nodes. The results of communication using the nRF24L01 module from the sensor node to the server with a peer to peer communication model in Line of Sight conditions can communicate at a maximum distance of 120 meters with an average delay of 6.98s and packet loss when sending data as much as 14% which is included in the bad category according to ITU -T G.114. Then to determine the quality of the network when sending data from the server to firebase with Wireshark software, a delay of 261ms was obtained, then for packet loss, the value of 8.3% was found to be in a suitable category according to ITU-T G.114.